1992
DOI: 10.1111/j.1464-410x.1992.tb15665.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Flow Rates in Patients with Benign Prostatic Hypertrophy following Treatment with Alfuzosin

Abstract: In order to document further the onset of action of alfuzosin, a selective alpha-1 blocker, 93 symptomatic patients with benign prostatic hypertrophy were randomly allocated to a single oral dose of either alfuzosin 1.25 mg or 2.5 mg, or placebo, after a 1-week placebo lead-in period. The effects on flow rates were assessed 1 h 30 min after administration. Peak and mean flow rates were significantly increased in the alfuzosin groups, as compared with placebo, in a dose-dependent manner. After a single intake o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 20 publications
4
16
0
1
Order By: Relevance
“…dizziness, hypotension/orthostatic hypotension and malaise) was similar to that observed with finasteride. These results are in accordance with those from previous studies on alfuzosin [1, 2, 7, 13, 14, 15]and differ from the VA study which showed that terazosin, alone or in combination with finasteride, was associated with incidences of orthostatic hypotension, dizziness and asthenia four, three and two times greater, respectively, than those observed with finasteride alone or placebo [8]. Hence, the present study confirms the clinical uroselectivity of SR alfuzosin (i.e.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…dizziness, hypotension/orthostatic hypotension and malaise) was similar to that observed with finasteride. These results are in accordance with those from previous studies on alfuzosin [1, 2, 7, 13, 14, 15]and differ from the VA study which showed that terazosin, alone or in combination with finasteride, was associated with incidences of orthostatic hypotension, dizziness and asthenia four, three and two times greater, respectively, than those observed with finasteride alone or placebo [8]. Hence, the present study confirms the clinical uroselectivity of SR alfuzosin (i.e.…”
Section: Discussionsupporting
confidence: 83%
“…α 1 -Blockers, such as sustained release (SR) alfuzosin, act on the dynamic component of obstruction by decreasing the sympathetically controlled tone of prostatic smooth muscle. They are characterized by a rapid onset of action, with evidence of efficacy from the first dose [7]. 5α-Reductase inhibitors, such as finasteride, block the conversion of testosterone to dihyrotestosterone, resulting in a reduction in prostate volume.…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawals caused by lack of efficacy were significantly higher in placebo patients than in those who received alfuzosin (14.6 and 6.8%, respectively, p<0.004) [35], and efficacy is apparent from the first dose [40]up until 30 months of therapy [41, 42]. A proven slow–release formulation (alfuzosin SR) now allows twice daily dosing [39].…”
Section: Resultsmentioning
confidence: 99%
“…Alfuzosin has been shown to improve maximum urinary flow rates (Q max ) from the first dose in two placebo-controlled studies [15, 16]. Dose-dependent increases in Q max at peak plasma concentration (90 min for the immediate release [IR] formulation; 180 min for the SR formulation) were observed (fig.…”
Section: Efficacy Of Alfuzosinmentioning
confidence: 96%